Tissue distribution study of perfluorooctanoic acid in exposed zebrafish using MALDI mass spectrometry imaging. (15th January 2022) - Bian, Yu; He, Mu-Yi; Ling, Yun; Wang, Xiu-Juan; Zhang, Feng; Feng, Xue-Song; Zhang, Yuan; Xing, Shi-Ge; Li, Jie; Qiu, Xin; Li, Yu-Rui
Abstract: Perfluorooctanoic acid (PFOA) as an emerging environmental contaminant, has become ubiquitous in the environment. It is of significance to study bioconcentration and tissue distribution of aquatic organisms for predicting the persistence of PFOA and its adverse effects on the environment and human body. However, the distribution of PFOA in different tissues is a complex physiological process affected by many factors. It is difficult to be accurately described by a simple kinetic model. In present study, a new strategy was introduced to research the PFOA distribution in tissues and estimate the exposure stages. Zebrafish were continuously exposed to 25 mg/L PFOA for 30 days to simulate environmental process. Matrix-assisted laser desorption ionization mass spectrometry imaging (MALDI-MSI) method was used to monitor the spatio-temporal distribution of PFOA in zebrafish tissues. By analyzing the law of change obtained from the high spatial resolution MSI data, two different enrichment trends in ten tissues were summarized by performing curve fitting. Analyzing the ratio of two types of curves, a new "exposure curve" was defined to evaluate the exposure stages. With this model, three levels (mild, moderate, and deep pollution stage) of PFOA pollution in zebrafish can be simply evaluated. Graphical abstract: Image 1 Highlights: A MSI analytical strategy was introduced to environmental exposure analysis. A zebrafish tissue-specific toxicokinetic model of PFOA was established. An exposure curve with three pollution levels was defined to judge pollution degree.